ANALISIS BUTIR SOAL UJIAN SEMESTER GANJIL PELAJARAN KIMIA KELAS X DI SMA/MA SEKECAMATAN PEKAITAN - indra bagus; Pangoloan Soleman Ritonga (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
AbstractThis research is motivated by chemistry exam of the odd semester in the school year of 2015/2016 which has not been validated. It is aimed at finding out the compatibility of semester exam reviewing from qualitative and quantitative. The techniques of data collections are interview and documentation. The data sources are multiple choice semester exam questions, students’ answer sheets, answer keys, question overview, lesson plan, and syllabus. The result of research is found that 12 questions of SMA and 11 questions of MA which is not compatible with the aspect being reviewed. The other result of research is found that SMA questions have the reliability of 0.5764 and MA as much as 0.80. By empirical validity, there are 25 SMA questions and 18 MA questions which are invalid. This research implication is all items of question must validated to know the quality of that items. Keywords: Chemistry education, Question Item Analysis